Use of Coal Bottom Ash as Mechanical Stabiliser in Subgrade Soil - Abdus Salaam Cadersa; Akshay Kumar Seeborun; Andre Chan Chim Yuk (Journal of Engineering)
This paper presents the laboratory investigation work which forms part of a full scale research road project in Mauritius where coal bottom ash is used as mechanical stabiliser in a saprolitic subgrade soil. Three mixtures of subgrade soil and CBA were investigated in the laboratory, each containing varying percentages of coal bottom ash by weight (15%, 30%, and 40%, resp.). The laboratory research indicated that the mechanical properties of the subgrade soil are improved with the addition of bottom ash. Highest values for soaked and unsoaked CBR values were obtained for the mixture containing 30% by weight of bottom ash, which were 145% and 95%, respectively, as compared to 40% and 55% for the subgrade soil alone. Upon addition of coal bottom ash, a considerable decrease in swelling potential during soaking was observed for the mixture containing 40% by weight of CBA. The swell decreased from 0.17% for the subgrade soil alone to 0.04% for the mixture containing 40% by weight of CBA. Moreover, a CBA content of 30% resulted in a mix of intermediate plasticity as compared to the subgrade soil which is highly plastic. It is concluded that coal bottom ash can be used successfully as a mechanical stabilizer in the experimental subgrade soil by addition of 30 to 40% of CBA.